Effects of early physical therapy on the rehabilitation of children with ASD: a systematic review (Research, Society and Development, 2022)
Introduction: Autism Spectrum Disorder (ASD) has no cure, nor a defined cause, and may inhibit the child's speech development, communication processes, interaction and social behavior. Physiotherapy has been of paramount importance for less dependence or even the achievement of independence for these children. In the rehabilitation of children with ASD, physiotherapy, through its resources and assisted activity, has shown improvement in neurological functioning at a cognitive, affective and motor level. Objective: to present how the scientific literature reports the effects of early physical therapy within a multidisciplinary and interdisciplinary approach in the rehabilitation of children with ASD. Methodology: A systematic review was carried out using the following databases - LILACS, MEDLINE, SCIELO AND CAPES PERIODIC, from 2009 to 2021; in English, Portuguese and Spanish. Conclusion: Through early physical therapy, children with ASD are able to achieve greater independence in their daily activities and an improvement in their neuropsychomotor development as a whole.